PELATIHAN UNTUK PELATIH BANTUAN HIDUP DASAR TAHUN 2023 DI DAERAH ISTIMEWA YOGYAKARTA - Nila Siwi, Ignasia; Jamaluddin, Ahmad; Eka Putra Suwarto, Dian; Ahliy Muhammad, Nur (ABDIMAS Madani, 2023)
Emergencies and disasters can happen anywhere and anytime. These conditions require first aid in order to minimize morbidity and mortality. First aid is obtained through basic life support training provided by trainers. A first aid trainer requires training in basic life support trainers in order to be able to train first aiders. Training for basic life support trainers is carried out with the aim of preparing prospective trainers who are able to teach knowledge and skills to first aiders. The methods used in the training for trainers are lectures, simulations and demonstrations. The results of the training showed that 45.45% (10 participants) passed the written and practical exams, 45.45% (10 participants) only passed the practical exams and 9% (2 participants) only passed the written exam. The conclusion of the training was that not all the participants who took part were able to pass the written and practical exams so that they needed re-participation as participants in the same activity.